Psychological variables in pregnancy : does age matter? An exploratory study - Pereira, M. Graça (2002)
We are assintng in our days to a postponing of pregnancy to a later period of life. This paper describes an exploratory study on the effects of age on important psycohological variables in pregnancy. The sample is composed of two groups of pregnant women : above and below 35 years, and compared how these women differed on maternal adjustmnet, marital satisfaction and psychological morbidity. Husbands/partners of these women were also included in the sample and a comparison between the couple was also assessed on the first two variables. Results showed that younger women were better adjusted and had higher marital satisfaction. No differences were reported in terms of psychological morbidity. Men reported being better adjusted than their partners on attitudes towards pregnancy. Differences on whether the pregnancy was planned and number of children were also assessed. Implications of study are discussed.